DEMOGRAPHIC AND PREDICTOR FACTORS OF SEVERE DENGUE IN CHILDREN AT SUMBER WARAS HOSPITAL: A RETROSPECTIVE OBSERVATIONAL STUDY - Sais, Vira Cendana; Sari, Meiriani; Halim, Hendy; Alfara, Lady Dhita (E-Jurnal Medika Udayana; Vol 13 No 11 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i11.P04, 2024)
ABSTRACT Background : Dengue prevalence is still high worldwide, as well as in Indonesia. Jakarta is the second province with the most dengue cases in early 2024. Funding and cost constraints hinder dengue diagnosis. This study aims to determine the demographics of dengue cases and predictive factors of severe dengue without diagnostic laboratory examination. Patients and Methods: This was a retrospective observational study of pediatric patients at Sumber Waras Hospital Jakarta from January-June 2024. Inclusion criteria were probable dengue respondents without dengue diagnostic examination. Data in the form of home address and various predictors of severe dengue were then analyzed univariate and multivariate (chi-square, Fisher exact test, and binary logistic regression), with p value <0.05 considered significant. Results: There were 162 cases, with 115 dengue cases with warning signs and 47 severe dengue cases; there were 2 deaths in severe dengue. Grogol Petamburan district, especially Grogol urban village, is the area with the highest proportion. Predictors of severe dengue in univariate analysis were age, lethargy, persistent vomiting, abdominal pain, mucosal bleeding, hepatomegaly, clinical fluid accumulation, hematocrit >40%, platelets count <50,000/mm 3 + hematocrit >40%, and platelets count <20,000/mm 3 . On the other hand, multivariate analysis found lethargy, abdominal pain, mucosal bleeding, hepatomegaly, and hematocrit >40% were predictors of severe dengue (p-value <0.05). Conclusion: Although with limited laboratory examination,d monitoring of dengue warning signs, periodic platelet and hematocrit examination can be a predictor of severe dengue according to WHO 2009 criteria. Larger-scale studies are needed to confirm the predictive factors of severe dengue.   Keywords: dengue, demographic, predictive factors